The Portrayal of the Pre-Islamic Arabs as Murderers of Their Own Infants - Lindstedt, Ilkka (Approaching religion, 2026)
This article critically reassesses the accounts of the supposed custom of infanticide, particularly female infanticide (in Arabic, wa’d al-banāt), among pre-Islamic Arabs, arguing that this notion emerged during the Umayyad era as an imagined aspect of the so-called pre-Islamic jāhiliyya ("age of ignorance"). Both noble aspects, such as valour and esteemed poetry, and debased ones, such as polytheism and immorality, were ascribed to pre-Islamic Arabs, thus encapsulating a troublesome heritage. Additionally, this article explores some aspects of the Islamic-era political dynamics, particularly the polemics between various Arabian tribes. The case of the tribe of Tamīm—who are said to have been the main perpetrators of infanticide—is examined, highlighting how inter-tribal polemics influenced the birth and popularization of tales depicting the Tamīm as engaged in the brutal practice of daughter-killing. In my interpretation, the Tamīm became the butt of these polemical attacks because they fought on the losing side during the second Muslim fitna, "civil war" (680-92 CE). I argue that the sustained recollection and retelling of the jāhiliyya narratives served not only to forge a new Muslim identity and self-assertion of moral reformation but also to facilitate intra-Arab distinctions in Islamic times. Social Identity Theory (SIT) serves as the interpretive framework of the article